REPRESENTASI NILAI SOSIAL BUDAYA DALAM CERITA ANAK BERJUDUL NONA BUPU: ANALISIS SEMIOTIKA ROLAND BARTHES DAN RELEVANSINYA DALAM PEMBELAJARAN BAHASA INDONESIA - Masita; Ramly; Sahtiani Jahrir, Andi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the representation of social and cultural values in the digital children’s story Nona Bupu: Pemandu Cilik dari Lereng Gunung Inerie and its relevance to Indonesian language learning in elementary schools. This study employs a descriptive qualitative approach using Roland Barthes’s semiotic analysis through the stages of denotation, connotation, and myth. The results of the study indicate the presence of social values such as discipline, responsibility, cooperation, social concern, and tolerance, as well as cultural values such as pride in local identity, respect for customs, and the preservation of Bajawa community traditions. These values are interpreted as naturalized myths through the characters’ actions and the plot and are relevant in Indonesian language learning in elementary schools to support the strengthening of literacy, character education, and cultural appreciation in accordance with the Merdeka Curriculum.